RITUS RUWAT: ESENSIALISME BARU DALAM POLITIK KEBUDAYAAN INDONESIA - Ninuk Kleden-Probonegoro (LIPI Press, 2008)
Ruwat is one of the ceremonies in Javanese tradition, which is conducted in accordance to the culture’s cosmology. In Javanese cosmology, changes or transfers are considered as dangerous, and therefore a ceremony is performed to liberate the individual from such dangers. As a ritual, Ruwat is always conducted every 1st Suro according to the Javanese calendar or 1st Muharram according to the Islamic calendar. In its development, cultural agents have brought Ruwat outside its original scope. Ruwat is no longer practiced within Javanese circles only but also within public circles and attracts tourism and commodities. In addition, Ruwat is also practiced at a national scope, especially in ceremonies blessing the work of political leaders. Ruwat, which was given and practiced within Javanese private sphere has transformed to the public sphere. It is now practiced even within the scope of the nation state, which is not given but constructed. This article explains the dynamics of shift from private to public; and from sacral to profane purposes practiced in the scope of the nation state.